Synthesis of cobalt ferrite nanoparticles by constant pH co-precipitation and their high catalytic activity in CO oxidation. (29th June 2017) - Thomas, Jasmine; Thomas, Nygil; Girgsdies, Frank; Beherns, Malte; Huang, Xing; Sudheesh, V. D.; Sebastian, Varkey
Abstract : A series of cobalt ferrite samples were synthesized from a metal nitrate solution at constant pH between 9 and 12 by the controlled co-precipitation method without any surfactant. Abstract : A series of cobalt ferrite samples were synthesized from a metal nitrate solution at constant pH between 9 and 12 by the controlled co-precipitation method without any surfactant. Cobalt and iron nitrates and sodium hydroxide base were simultaneously dosed so that the pH was precisely controlled during co-precipitation. The samples were characterized by PXRD, SEM, TEM, BET, and TPR. Careful analysis of typical PXRD peak profiles suggested the presence of two different variants of cobalt ferrite, a nano-scale material giving rise to broad peak tails and a more crystalline material leading to a sharper central profile. Rietveld refinement could be used to quantify the relative amount of both nano and crystalline fractions in these samples indicating that their relative abundance can be controlled by the co-precipitation pH. TEM analysis further proved the presence of both crystalline and nanocrystalline region in the samples. The average crystallite size of the cobalt ferrite nanocrystallites was 4–5 nm. These samples exhibit high BET surface area, in the order of 200 m 2 g −1 . The samples were tested for catalytic performance in the CO oxidation reaction. The surface area, reduction behavior, and catalytic performance of ferrites were dependent on the relative amount of both the crystalline and nanocrystalline phases.